Penggunaan Artificial Neural Network untuk Memprediksi Inflasi Jawa Barat pada Tahun 2023 - Putri Zahiratul Muslimah; Herlina, Marizsa (Bandung Conference Series: Statistics, 2024)
Abstract. Forecasting is the process of predicting the magnitude or amount of something in the future based on scientific analysis of past data. One method of forecasting is Artificial Neural Network (ANN), which uses a simple mathematical model that mimics the way the human brain works. ANNs work by accepting inputs in various formats, then multiplying each input by a certain weight. The purpose of forecasting is to get a picture of future values that are useful for decision-making or anticipation in the present. This research aims to forecast inflation in West Java. Inflation is a generalized increase in the prices of goods and services that is sustained over a period of time, reflecting excessive and unstable monetary growth. The data used in this study is West Java inflation data from 2013 to 2022 with a monthly period. With the proportion of training and testing data of 70:30, this research produces a multi-layer artificial neural network architecture design consisting of 3 layers, namely 3 neurons in the input layer (based on the PACF plot), 3 neurons in the hidden layer (based on the best MSE value), and 1 neuron in the output layer. The parameters used in this model include a learning rate of 0.5 and a binary sigmoid activation function. Abstrak. Peramalan merupakan proses memprediksi besarnya atau jumlah sesuatu di masa depan berdasarkan analisis ilmiah terhadap data masa lalu. Salah satu metode peramalan ialah Artificial Neural Network (ANN) atau jaringan saraf tiruan, yang menggunakan model matematika sederhana yang meniru cara kerja otak manusia. ANN bekerja dengan menerima input dalam berbagai format, lalu mengalikan setiap input dengan bobot tertentu. Tujuan dari peramalan adalah untuk mendapatkan gambaran nilai di masa depan yang berguna untuk pengambilan keputusan atau antisipasi di masa kini. Penelitian ini bertujuan untuk meramalkan inflasi di Jawa Barat. Inflasi ialah peningkatan harga barang dan jasa secara general yang berlangsung secara berkelanjutan dalam periode tertentu, mencerminkan pertumbuhan moneter yang berlebihan dan tidak stabil. Data yang digunakan dalam penelitian ini adalah data inflasi Jawa Barat dari tahun 2013 hingga 2022 dengan periode bulanan. Dengan proporsi data training dan testing sebesar 70:30, penelitian ini menghasilkan rancangan arsitektur jaringan saraf tiruan multi-layer network yang terdiri dari 3 layer, yaitu 3 neuron pada input layer (berdasarkan plot PACF), 3 neuron pada hidden layer (berdasarkan nilai MSE terbaik), dan 1 neuron pada output layer. Parameter yang digunakan dalam model ini meliputi learning rate sebesar 0,5 dan fungsi aktivasi sigmoid biner.